2022
DOI: 10.3389/fmolb.2022.870460
|View full text |Cite
|
Sign up to set email alerts
|

Legume Plant Peptides as Sources of Novel Antimicrobial Molecules Against Human Pathogens

Abstract: Antimicrobial peptides are prominent components of the plant immune system acting against a wide variety of pathogens. Legume plants from the inverted repeat lacking clade (IRLC) have evolved a unique gene family encoding nodule-specific cysteine-rich NCR peptides acting in the symbiotic cells of root nodules, where they convert their bacterial endosymbionts into non-cultivable, polyploid nitrogen-fixing cells. NCRs are usually 30–50 amino acids long peptides having a characteristic pattern of 4 or 6 cysteines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…The use of human blood for the hemolysis assay has been authorized by the Regional Hungarian Ethics Committee and approved by the Ethics Review Sector of DG RTD (European Commission) in connection with EK's ERC AdG SymBiotics. The protocol was performed as described by Lima et al [30]. Baseline OD 560 values were determined with cells in TBS buffer, while 0.5% Triton X-100 (Serva) was added to the cells at the same time as NCRs represented 100% of hemolysis.…”
Section: Hemolysis Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…The use of human blood for the hemolysis assay has been authorized by the Regional Hungarian Ethics Committee and approved by the Ethics Review Sector of DG RTD (European Commission) in connection with EK's ERC AdG SymBiotics. The protocol was performed as described by Lima et al [30]. Baseline OD 560 values were determined with cells in TBS buffer, while 0.5% Triton X-100 (Serva) was added to the cells at the same time as NCRs represented 100% of hemolysis.…”
Section: Hemolysis Assaymentioning
confidence: 99%
“…For example, the 24-amino-acid-long NCR247 peptide, together with its derivates, displayed promising antimicrobial activity against several bacterial strains including ESKAPE pathogens [28]. A recent publication from our group revealed that among 104 synthetic NCR peptides from M. truncatula, M. sativa, Pisum sativum, Galega orientalis, and Cicer arietinum, almost all cationic peptides displayed a broad antimicrobial spectrum, as well as the effective and rapid killing of ESKAPE bacteria within a minimal bactericidal concentration (MBC) range of 0.8-3.1 µM [30].…”
Section: Introductionmentioning
confidence: 99%
“…Antimicrobial peptide-based therapy, suggested by and developed from the multitude of insects, plants, and other organisms that make daily use of them for survival [50][51][52][53], showed a minor insurgence of antibiotic resistance due to the intrinsic multi-modal, multitarget action derived from the more complex structure of these compounds, and a plethora of co-adjuvant properties such as antioxidant, anti-inflammatory, and pro-healing effects [54,55]. However, their application in therapy is restricted because of their side effects, caused by off-target reactions with human epitopes and by the high concentration (derived from their conspicuous molecular weight) at which they need to be administered to exert their properties.…”
Section: Polymixinsmentioning
confidence: 99%